1995
DOI: 10.1097/00005392-199510000-00091
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Crystal Growth of Calcium Oxalate in Gel and its Modification by Urinary Constituents in a New Flow Model of Crystallization

Abstract: Drinking therapy and lowering of urinary oxalate excretion can be concluded to be the most promising means of preventing CaOx urolithiasis. The new crystallization model demonstrated here should be suitable to new applications in the investigation of urinary stone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Urinary stones grow in a gel like medium; therefore, they have radially striated growth [16] . The crystal growth by gel method provides simulation of synovial cartilage and other biological fluids [17] . Gel growth (in vitro) of a few urinary stone constituents and the inhibitory role played by some extracts or juices of natural products in crystal growth were studied earlier [18] .…”
Section: Single Diffusion Gel Growth Techniquementioning
confidence: 99%
“…Urinary stones grow in a gel like medium; therefore, they have radially striated growth [16] . The crystal growth by gel method provides simulation of synovial cartilage and other biological fluids [17] . Gel growth (in vitro) of a few urinary stone constituents and the inhibitory role played by some extracts or juices of natural products in crystal growth were studied earlier [18] .…”
Section: Single Diffusion Gel Growth Techniquementioning
confidence: 99%
“…Depending on the special conditions applied, fixed crystal nucleation, growth and agglomeration, as well as effects upon these parts of crystallisation, can be directly observed by light microscopy. Crystal growth of CaOx could be quantified in this system by following scattered light as a function of time [4]. Phenomena of epitactic growth could be investigated by overgrowth of one crystal phase with another [5].…”
Section: Discussion On the Physiological Relevance Of In Vitro Crystamentioning
confidence: 99%
“…Nucleation rates, surprisingly, were significantly higher in normals than in stone patients. Achilles et al [4], applying the GCM described above, demonstrated a higher growth rate for CaOx in undiluted urine of male stone formers than for matched controls. Though this difference was clearly significant (P < 0.01), the overlap of single values from both groups led to the conclusion that factors additional to those affecting crystal growth are likely to be responsible, at least in part, for the genesis of CaOx urolithiasis.…”
Section: Relative Importance Of Parameters Of Crystallisation In Stonmentioning
confidence: 92%
See 1 more Smart Citation
“…The case of insufficient intake of water or due to the decreased rate of excretion, the crystallogenic substances in the urine can be concentrated, leading to crystal formation. A change in the pH value in the urine can lead to the crystal growth (5,6). Humans are exposed to cadmium is if no use to the human body and is toxic even at low levels.…”
Section: Introduction:-mentioning
confidence: 99%